Voting Behavior Of Indigenous Minorities In Local Elections: Kampa Community In Pasaman - Afriandi, Fadli; Latif, Ikhwan Rahmatika; Abdillah, Ligar; Ariyadi, Fachriza; Nugroho, Sapto Setyo (Universitas Riau Kepulauan, 2025)
Voting behavior is an important part of the democratic process which can investigate the factors that influence constituents in choosing leaders. The purpose of this paper is to find out how the voting behavior of indigenous minority communities in determining leaders. The indigenous minority community is the object of research, which means that the community is part of the indigenous ethnic element but because of its origin from another area, it is considered a migrant. The main argument of this paper is that Kampa people choose regional heads influenced by sociological factors based on the social environment. This research is a qualitative study using the Social Circle Theory by George Simmel. In this study, data was collected using primary data through direct interviews, and secondary data was collected through scientific journals and online mass media. The results of the study found that the voting behavior of the Kampa community was influenced by first, namely political preferences which vote based on considerations from traditional leaders, second geopolitics where geographically the area inhabited is the majority of Minangkabau tribes, and third based on socio-economic structures that influence rational reasons for choosing regional heads.